Rethinking human nature : a Christian materialist alternative to the soul - Corcoran, Kevin, 1964- (2006)
Kevin J. Corcoran argues that the "Christian story, with embodiment and incarnation at its center, provides the theological backdrop against which to measure our view of human nature." With this backdrop in mind Corcoran contends for a view of human nature that steers a middle way of sorts between dualism and strict materialism. The result is a nuanced Christian materialism, the Constitution View, that Corcoran believes best fits the "earthy picture of the Bible's grand narrative." Through arguing for this conclusion and addressing concerns it raises, Corcoran provides a solid introduction to the main debates regarding human nature that is infused with current scholarly debate on these topics and presented with an admirable scholarly humbleness.
Introduction: what kind of things are we? -- Dualist views of human persons -- Nothing-but materialism -- The constitution view -- The stem cell challenge -- I believe in the Resurrection of the body and the life of the world to come -- The constitution view and the bible: some final thoughts.
Includes bibliographical references and index.
Keywords: Philosophical anthropology; Theological anthropology -- Christianity; Christianity -- Philosophy